The young generation as the vanguard of democratic change in Central Europe - Poniedziałek, Jacek (Eastern European Countryside, 2024)
The aim of this article is to analyse the results of a youth study carried out in selected post-communist countries in Central Europe, published in the mono- graph The Me-Generation in a Post-Collectivist Space. Dilemmas in a Time of Transition. Its authors ask a question about the role of the young generation in the processes of systemic transformation. Their research reveals that young people have little involvement in public life, rarely participate in elections, and are mostly preoccupied with individual strategies and satisfying their own needs. Those who show an interest in public affairs and actively participate in political life tend to contest the idea of liberal democracy, and support nationalist and populist parties; they blame democracy for failing to fulfil their aspirations. This type of youth generates social changes that contribute to the strengthening of na- tionalist and anti-European trends in Central Europe. Nevertheless, conclusions presented in the study seem to be overly pessimistic, as there are also groups of young people who present post-materialist attitudes and who are interested in the democratisation of the political systems in their countries.